Antipsychotics in schizophrenia: a retrospective study of drug utilization pattern in outpatient department of psychiatry at a tertiary care hospital - Patted, Usharani H.; G., Hema N.; Nagaraj, Anil Kumar Mysore (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Psychiatric disorders are one of the major causes of morbidity and the burden of illness is enormous and remains grossly under represented. Psychotropic drugs have had a remarkable impact in psychiatric practice. Currently a large number of atypical antipsychotics available in the market are endorsed as better options for treating schizophrenia than the typical antipsychotics. The main objective of the study was to find the commonly prescribed antipsychotics in schizophrenia patients in a tertiary care center. Methods: After Institutional Ethics Committee approval, a retrospective cross-sectional drug utilization study of 400 prescriptions was under taken from 1st July 2015 to 30th July 2016 in the outpatient department of psychiatry of a tertiary care hospital. The prescribing pattern of antipsychotics in schizophrenia patients (N=107) was measured. Results: Out of 400 cases in the outpatient department, schizophrenia cases were predominant (N=107 i.e. 27%) out of which 42.1% were females and 57.9% were males. This was followed by mood disorders and neurotic & somatoform disorders. The most common antipsychotic used was olanzapine followed by risperidone. Least commonly used antipsychotic was haloperidol. Most of the patients who received risperidone also received an anticholinergic trihexyphenidyl (91.8%). Conclusions: Olanzapine and risperidone are the most commonly used antipsychotics. Anticholinergics should be used only in selected patients on antipsychotics as tolerance develops to extrapyramidal side effects. Anticholinergics are unnecessary after 3-6 months in all except 10% of patients. Moreover, it has its own side effects and adversely interacts with antipsychotics.